2007
DOI: 10.1177/000348940711601107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early-Stage Glottic Cancer by Transoral Laser Resection

Abstract: Laser microresection provides high rates of local control and organ preservation for early glottic cancer. Positive or suspicious margins were not related to recurrence, nor was anterior commissure involvement. This study implies that suspicious margins can be managed with a "watch-and-wait" attitude. Re-treatment with laser, external partial laryngectomy, and radiotherapy remain therapeutic options for recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 19 publications
12
85
2
Order By: Relevance
“…In the literature, local control rates for radiotherapy are reported between 78% and 94% 10,15,16 and for CO 2 laser surgery between 77% and 95%. 4,[8][9][10]17 Our 5-year local control rates are somewhat lower than the local control rates found in the literature. A possible explanation might be that other authors reported a 3-year local control rate and included Tis carcinomas in their group.…”
Section: Figurecontrasting
confidence: 82%
See 2 more Smart Citations
“…In the literature, local control rates for radiotherapy are reported between 78% and 94% 10,15,16 and for CO 2 laser surgery between 77% and 95%. 4,[8][9][10]17 Our 5-year local control rates are somewhat lower than the local control rates found in the literature. A possible explanation might be that other authors reported a 3-year local control rate and included Tis carcinomas in their group.…”
Section: Figurecontrasting
confidence: 82%
“…A possible explanation might be that other authors reported a 3-year local control rate and included Tis carcinomas in their group. 4,8,17 In the current study, we showed that patients with T1a glottic laryngeal carcinoma treated primarily with CO 2 laser surgery had a significantly better 5-year laryngeal preservation rate (95%) than patients treated with radiotherapy (77%), despite the lack of difference in local control. For the CO 2 laser group, our 5-year laryngeal preservation rate is in concordance with previously published results.…”
Section: Figurementioning
confidence: 46%
See 1 more Smart Citation
“…Each excision can be adapted individually to the size of the tumour allowing the establishment of final diagnosis and therapy at the same time. For glottic CIS, data reported on local control vary between 76 and 100% with larynx preservation in more than 92% of cases [15,16,[18][19][20][21][22][23][24][25] ( table 2 ). In the present series, our data on local control confirm the favourable results obtained in previous studies recommending TLM as the method of choice in cases of glottic CIS when endoscopic exposition poses no greater difficulties to the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Ansarin 5 reported that patients with close or positive margins had greater recurrence risk. The few studies [6][7][8][9] that have addressed the impact of margin status on local control in malignant vocal cord neoplasms have provided contrasting results.…”
Section: Introductionmentioning
confidence: 99%